Psychoanalysis as a spiritual discipline in dialogue with Martin Buber and Gabriel Marcel - Marcus, Paul 1953- (Routledge, Taylor & Francis Group, 2021)
"In chapters that focus on love, work, faith, suffering, and clinical practice, Paul Marcus shows how the spiritual optic of Buber and Marcel can help revive and refresh psychoanalysis, and bring it back into the light by communicating its inherent vitality, power, and relevance to the mental health community and to those who seek psychoanalytic treatment"--
Keywords: Buber, Martin -- 1878-1965; Marcel, Gabriel -- 1889-1973; Religionsphilosophie; Psychoanalyse; Religion; Spiritualität; Psychotherapie; Psychoanalysis and religion; Buber, Martin / 1878-1965; Marcel, Gabriel / 1889-1973